Meningococcal ACWY conjugate vaccine immunogenicity in adolescents with primary or secondary immune deficiencies, a prospective observational cohort study - Milou Ohm; Joeri W van Straalen; Gerrie de Joode-Smink; Joris van Montfrans; Marije Bartels; Joanne G van Wildenbeest; Caroline A Lindemans; Roos AW Wennink; Joke H de Boer; Elisabeth AM Sanders; Frans M Verduyn-Lunel; Guy AM Berbers; et al. (Pediatric Rheumatology Online Journal, 2023)
Abstract Background Immunization with meningococcal ACWY conjugate vaccine induces protective antibodies against invasive meningococcal disease (IMD) caused by serogroups A, C, W and Y. We studied MenACWY-TT vaccine immunogenicity in adolescents with a heterogenous group of primary and secondary immune deficiency including patients with systemic lupus erythematosus, mixed connective tissue disease, vasculitis, uveitis, 22Q11 syndrome, sickle cell disease, and patients who underwent stem cell transplantation for bone marrow failure. Findings We enrolled 69 individuals aged 14–18 years diagnosed with a primary or secondary immune deficiency in a prospective observational cohort study. All patients received a single dose of MenACWY-TT vaccine during the catch-up campaign 2018-19 because of the IMD-W outbreak in the Netherlands. Capsular polysaccharide-specific (PS) IgG concentrations against MenACWY were measured before and 3–6, 12, and 24 months after vaccination. Overall, geometric mean concentrations (GMCs) of MenACWY-PS-specific IgG were lower in patients compared to data from healthy, aged-matched controls (n = 75) reaching significance at 12 months postvaccination for serogroup A and W (adjusted GMC ratios 0.26 [95% CI: 0.15–0.47] and 0.22 [95% CI: 0.10–0.49], respectively). No serious adverse events were reported by study participants. Conclusions The MenACWY conjugate vaccine was less immunogenic in adolescent patients with primary or secondary immunodeficiency compared to healthy controls, urging the need for further surveillance of these patients and supporting considerations for booster MenACWY conjugate vaccinations in these patient groups.